Development of a HPLC Method for the Quantitative Determination of Capsaicin in Collagen Sponge - Chun-Lian Guo; Hong-Ying Chen; Bi-Ling Cui; Yu-Huan Chen; Yan-Fang Zhou; Xin-Sheng Peng; Qin Wang (International Journal of Analytical Chemistry)
Controlling the concentration of drugs in pharmaceutical products is essential to patient’s safety. In this study, a simple and sensitive HPLC method is developed to quantitatively analyze capsaicin in collagen sponge. The capsaicin from sponge was extracted for 30 min with ultrasonic wave extraction technique and methanol was used as solvent. The chromatographic method was performed by using isocratic system composed of acetonitrile-water (70 : 30) with a flow rate of 1 mL/min and the detection wavelength was at 280 nm. Capsaicin can be successfully separated with good linearity (the regression equation is A = 9.7182C + 0.8547; R2 = 1.0) and perfect recovery (99.72%). The mean capsaicin concentration in collagen sponge was 49.32 mg/g (RSD = 1.30%; n = 3). In conclusion, the ultrasonic wave extraction method is simple and the extracting efficiency is high. The HPLC assay has excellent sensitivity and specificity and is a convenient method for capsaicin detection in collagen sponge. This paper firstly discusses the quantitative analysis of capsaicin in collagen sponge.